Functional characterization of the defective CYP2C9 variant CYP2C9*18 - Jian Liu; Hao Chen; Shuang‐Hu Wang; Quan Zhou; Pei‐Wu Geng; Yun‐Fang Zhou; Hua‐Lan Wu; Hai‐Feng Shi; Fang Wang; Jie‐Fu Yang; Jian‐Ping Cai; Da‐Peng Dai (Wiley, 2021)
Abstract Cytochrome P450 2C9 (CYP2C9) is one of the most important drugs metabolizing enzymes and accounts for the metabolism of about 13%-17% of clinical drugs. Like other members in CYP2 family, CYP2C9 gene exhibits great genetic polymorphism among different races and individuals. CYP2C9*18 is one CYP2C9 allelic variant identified in a Southeast Asian population and is estimated to cause the amino acid substitutions of I359L and D397A in CYP2C9 enzyme simultaneously. Limited by the low expression level in bacteria and COS‐7 cells, no valuable enzyme kinetics have been reported on this CYP2C9 variant. In this study, the baculovirus‐based system was used for the high expression of recombinant CYP2C9 s in insect cells. As a result, together with I359L substitution, D397A could significantly decrease the protein expression of CYP2C9.18 in insect cells, although substitution of D397A alone had no effect on the expression of CYP2C9 in vitro. As compared with that of wild‐type enzyme, both CYP2C9.18 variant and D397A variant could decrease more than 80% of the catalytic activity of CYP2C9 enzyme toward three probe substrates, suggesting that caution should be exercised when patients carrying CYP2C9*18 taking medicines metabolized by CYP2C9 enzyme with a narrow therapeutic window.